Performance Improvement of Concrete Pouring Process Based Resource Utilization Using Taguchi Method and Computer Simulation (Jurnal Teknologi (Sciences & Engineering), 2014)
One of the most controversial issues in construction management is performance measurement. Construction managers are always involved in evaluation of resource changes which effect process performance. Due to limitations and also cost of resources, resource allocation has become a complex task in construction projects. To evaluate the effects of different resources on total project performance, managers strive to allocate limited resources by determining resource combinations. This paper aims at conducting Taguchi method along with computer simulation to determine the optimum combination of resources for a real world case study involving a concrete pouring operation in order to reduce cycle time and process costs. The proposed simulation model was conducted under Arena 13.9. Final result shows that the optimum resource combination will be achieved when all of resources are located in the low level. This means that number of trucks, spreader crew, vibrator crew and finisher crew should be equal to 3, 1, 1, and 1 respectively to improve the total performance.